Experience and observation: from Rousseau to the National Curriculum Reference for Early Childhood Education (Educação e Pesquisa, 2011)
The article has as its objective to recover the concepts of experience and observation present in Jean-Jacques Rousseau's Émile, discussing them in the perspective of an education for emancipation, as it is formulated by the authors of the Critical Theory, specially Walter Benjamin and Theodor W. Adorno. Considering the use and valuation of these concepts in the theory and practice of education, the text analyzes the treatment given to them in the National Curriculum Reference for Early Childhood Education, with the purpose of highlighting the criticism present in the defense of children's experiences and of their observation in the school daily life. It concludes, based on reflections about Rousseau's texts and about those of the authors of the Critical Theory, that in the above-mentioned document, faced with the polysemy of the formative experience, emphasis is given to the curriculum aspect, to the instrumentalization of teachers' action, to experiences and learning labeled as essential, to the experience that the teacher affords to the children, and to the mapping of subjectivities through observation and systematic recording. If Rousseau asks us to observe the child, as well as to offer and value significant experiences, it is because somehow, making use of a theoretical-methodological resource, he is addressing concrete educators who, after almost three centuries, are still entangled by concepts and social representations of childhood, oblivious to the experience that legitimizes the construction of these same concepts and representations.